Keen's Approach: A Dynamic Approach for Zygomatic Arch Fracture Management - Mohan, Muralee; S., Tripthi P.; Shetty, Pratiksha; Menon, Akash (Journal of Health and Allied Sciences NU, 2016)
Maxillofacial fractures are often associated with blunt head injuries of which the outward projection of the Zygomatic Arch exposes it to frequent injury. Isolated Zygomatic arch fractures account for 10% of all Zygomatic bone fractures. Depressed Zygomatic arch fractures causes restricted mouth opening due to the partial or total obstruction of the movement of mandibular coronoid and condylar processes. Numerous techniques have been used to approach the site and reduce the fractured fragments, such as the Gillie's temporal approach, Keen's intraoral approach, anterior cheek skin incision and direct open approach.Below is a case report of an isolated Zygomatic arch fracture following a road accident in a middle aged woman that was surgically treated by open reduction through the Keen's intraoral approach. Successful reduction of the fractured segments and restoration of function was achieved with no scarring, minimal post-operative pain and satisfactory aesthetics.
Keywords: Zygomatic arch; Fracture; Intraoral approach; Gillie's technique